Identification of creat (Andrographis paniculata Ness) as basic for concervation and make use of germ plasm - TRIJONO DJOKO SULISTIJO; BAMBANG PUJIASMANTO (Biodiversitas Journal of Biological Diversity, 2007)
This research is to learn the creat potention for cultivated as medical material producer plant. So that, the limited creat as medical material not occur. The method of research which used is survey. The survai include identification and creat distribution pattern. There was used vegetative analysis with quadrat method. The research result showed that 1) in creat habitat find out 11 species of tree, 20 species herba (include creat), and 16 species grasses, 2) The highest of importance value indeks Tectona grandis L. (tree group), Andrographispaniculata Ness (herb group), and Portulaca oleraceae L. (grasses group), 3) Distribution pattern of creat is clumped, and the herb others is uniform, 4) The creat growth on the common under shading Tectona grandis L. tree. The results of this research are domestication concept and theories which to basic the cultivated technology packet of creat wild plant which the statue increased be medical material produce crop. In the next ,expected can used for get conclusion policy of medical crop and planning, especially on creat propertion of creatmedical material.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: identification of creat, concervation of germ plasm